2003
DOI: 10.5194/npg-10-323-2003
|View full text |Cite
|
Sign up to set email alerts
|

Classification of probability densities on the basis of Pearson’s curves with application to coronal heating simulations

Abstract: Abstract. An important task for the problem of coronal heating is to produce reliable evaluation of the statistical properties of energy release and eruptive events such as microand nanoflares in the solar corona. Different types of distributions for the peak flux, peak count rate measurements, pixel intensities, total energy flux or emission measures increases or waiting times have appeared in the literature. This raises the question of a precise evaluation and classification of such distributions. For this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…4) that could be characterized by a broken power law (see also Fig. 12 in Aschwanden et al 2000b), by an exponential rollover (Kadanoff et al 1989;Lu et al 1993;Charbonneau et al 2001), or by Pearson distributions (Podladchikova et al 2002). Deviations from pure power laws can also be seen in our synthesized frequency distributions (Figs.…”
Section: Discussion Of Methodical Uncertaintiesmentioning
confidence: 79%
“…4) that could be characterized by a broken power law (see also Fig. 12 in Aschwanden et al 2000b), by an exponential rollover (Kadanoff et al 1989;Lu et al 1993;Charbonneau et al 2001), or by Pearson distributions (Podladchikova et al 2002). Deviations from pure power laws can also be seen in our synthesized frequency distributions (Figs.…”
Section: Discussion Of Methodical Uncertaintiesmentioning
confidence: 79%
“…Preliminary results concerned with the influence of the type of magnetic field energy dissipation on statistical properties of the total radiation energy flux were presented by Podladchikova et al (1999). It was shown that the dissipated energy has approximately normal distribution when the source of the magnetic field is random and the dissipation is provided by anomalous resistivity.…”
Section: Resultsmentioning
confidence: 99%
“…While the laborious fitting procedure by the method of moments, made somewhat easier by ad hoc routines and tables [23], still finds some applications [24], Pearson's distributions are nowadays seldom resorted to, owing to later introduction of more user friendly families.…”
Section: Empirical Distributionsmentioning
confidence: 99%